2016
DOI: 10.1161/circinterventions.116.003613
|View full text |Cite|
|
Sign up to set email alerts
|

Assessing Computational Fractional Flow Reserve From Optical Coherence Tomography in Patients With Intermediate Coronary Stenosis in the Left Anterior Descending Artery

Abstract: Background-Intravascular optical coherence tomography (OCT) imaging provides limited information on the functional assessment of coronary stenosis. We evaluated a new approach to OCT image-based computation modeling, which can be used to estimate the fractional flow reserve (FFR) 14 The objective of this study was to present a new approach for estimating invasive FFR using OCT lumen contour-based 3D coronary models (FFR OCT ) and CFD algorithms. In addition, the clinical usefulness of FFR OCT was evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 26 publications
(35 reference statements)
0
39
1
3
Order By: Relevance
“…Ha et al reported that OCT-derived FFR, which depends on computational fluid dynamics, could accurately predict myocardial ischemia, and suggested that computational fluid dynamics might enable the assessment of functional information. 33 Although computational fluid dynamics is a useful method to calculate FFR, it requires a high-performance computer, long calculation time, and strict 3-D reconstruction of the coronary arteries. Therefore, FFR may be difficult to calculate in catheter laboratories in daily practice using computational fluid dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Ha et al reported that OCT-derived FFR, which depends on computational fluid dynamics, could accurately predict myocardial ischemia, and suggested that computational fluid dynamics might enable the assessment of functional information. 33 Although computational fluid dynamics is a useful method to calculate FFR, it requires a high-performance computer, long calculation time, and strict 3-D reconstruction of the coronary arteries. Therefore, FFR may be difficult to calculate in catheter laboratories in daily practice using computational fluid dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, intravascular imaging methods, which are known to provide accurate segmentation of the vascular lumen, raise as candidates to offer good‐quality images for computational estimations of coronary flow. Accordingly, a recent study using OCT‐based computational FFR resulted in an overall accuracy of 88.0% in detecting flow‐limiting lesions only in LAD arteries …”
Section: Discussionmentioning
confidence: 99%
“…Multimodality imaging, such as a combination between CT technology, 3-dimensional reconstruction of invasive imaging, and CFD technology enables precise simulation of coronary flow in a patient-specific coronary model, and provides non-invasive hemodynamic information to overcome the current ‘simple’ imaging-derived parameters for predicting lesion-specific functional significance. 44) 45) 46) 47) Further research on the role of precise imaging techniques is expected and needed. Finally, the body of clinical evidence on resting physiologic indices is rapidly growing, predominantly with instantaneous wave-free ratio (iFR).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%